Effects of amino‐functionalized carbon nanotubes on the properties of amine‐terminated butadiene–acrylonitrile rubber‐toughened epoxy resins. Issue 13 (11th February 2014) - Zhang, Jusheng; Wang, Yuting; Wang, Xiaoshan; Ding, Guowei; Pan, Youqiang; Xie, Hongfeng; Chen, Qingmin; Cheng, Rongshi
ABSTRACT Amino‐functionalized multiwalled carbon nanotubes (MWCNT‐NH2s) as nanofillers were incorporated into diglycidyl ether of bisphenol A (DGEBA) toughened with amine‐terminated butadiene–acrylonitrile (ATBN). The curing kinetics, glass‐transition temperature (Tg), thermal stability, mechanical properties, and morphology of DGEBA/ATBN/MWCNT‐NH2 nanocomposites were investigated by differential scanning calorimetry (DSC), thermogravimetric analysis, a universal test machine, and scanning electron microscopy. DSC dynamic kinetic studies showed that the addition of MWCNT‐NH2s accelerated the curing reaction of the ATBN‐toughened epoxy resin. DSC results revealed that the Tg of the rubber‐toughened epoxy nanocomposites decreased nearly 10°C with 2 wt % MWCNT‐NH2s. The thermogravimetric results show that the addition of MWCNT‐NH2s enhanced the thermal stability of the ATBN‐toughened epoxy resin. The tensile strength, flexural strength, and flexural modulus of the DGEBA/ATBN/MWCNT‐NH2 nanocomposites increased increasing MWCNT‐NH2 contents, whereas the addition of the MWCNT‐NH2s slightly decreased the elongation at break of the rubber‐toughened epoxy. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40472.